2004
DOI: 10.1159/000077102
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholesterol Affects Sympathetic Nerve Function in Rabbit Hearts

Abstract: In order to assess the effect of hypercholesterolemia on cardiac sympathetic nerve function, New Zealand white rabbits were fed a normal diet (the control group) or one enriched with 0.5% cholesterol [the hypercholesterol (HC) group] for 3 months. Before and after the 3-month diet treatment, we performed serial imaging examinations and analyzed the uptake and washout ratio of 123I-meta-iodobenzylguanidine (123I-MIBG) from the myocardium by administration of 123I-MIBG through an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Our previous studies showed that HC induced significant cardiac nerve sprouting and sympathetic hyperinnervation in both immunocytochemical studies in vitro and 123 I-MIBG imaging in vivo in HC rabbits 1,2. Furthermore, there is an excellent dose–response relationship between serum cholesterol level and nerve density for GAP43(+) and TH(+) nerves 1.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous studies showed that HC induced significant cardiac nerve sprouting and sympathetic hyperinnervation in both immunocytochemical studies in vitro and 123 I-MIBG imaging in vivo in HC rabbits 1,2. Furthermore, there is an excellent dose–response relationship between serum cholesterol level and nerve density for GAP43(+) and TH(+) nerves 1.…”
Section: Discussionmentioning
confidence: 97%
“…Significant upregulation of these markers has also been reported in a rabbit model with marked hypercholesterolemia . Once hyperinnervation begins, the incidence of VF was enhanced due to an increase in voltage‐gated Ca current, prolongation of action potential duration, and enlarged dispersion of repolarization time …”
Section: Discussionmentioning
confidence: 76%